Movements of Posyandu with stunting awareness theme - Putri, Melia Febrianty; Robani, Nida Nabila (Universitas Pendidikan Indonesia, 2023)
The health examination program is important for the community, especially for children at risk of stunting. Posyandu cadres are the main movers in all activities carried out by the Posyandu. It cannot be denied that the Posyandu cadre movement benefits its existence. In various regions in Indonesia, there is stunting, one of which is in Taringgul Tonggoh village located in Wanayasa sub-district, Purwakarta district. This may indicate the need for awareness regarding stunting from various parties. This service aims to discover out's role of Posyandu after the COVID-19 pandemic in preventing stunting rates in Wanayasa District, Purwakarta. Service activities by helping at different Posyandu on the 7th, 8th, 9th, and 10th follow different Posyandu schedules. The service results show four Posyandu, namely Posyandu Andita 1 and 2, Cihaur Mekar, and Peuntas Mekar, the stunting problem in Taringgul Tonggoh Village was recorded at 14 toddlers. Routine health checks, counseling, and providing additional food (PMT) are solutions to prevent increased stunting.